The Hidden Pathways in Dense Energy Materials – Oxygen at Defects in Nanocrystalline Metals. (17th September 2015) - Scherrer, Barbara; Döbeli, Max; Felfer, Peter; Spolenak, Ralph; Cairney, Julie; Galinski, Henning
<x xml:space="preserve">Abstract</x> Highly abundant oxygen‐rich line defects (blue) can act as fast oxygen transport paths. These defects show similar chemistry and therefore similar catalytic activity to the materials surface. These results provide the opportunity to design and produce simple scalable structures as catalysts, whose functionality derives from internal defects rather than from the materials surfaces.